2015
DOI: 10.1162/jocn_a_00740
|View full text |Cite
|
Sign up to set email alerts
|

Reinstatement of Individual Past Events Revealed by the Similarity of Distributed Activation Patterns during Encoding and Retrieval

Abstract: Neurobiological memory models assume memory traces are stored in neocortex, with pointers in the hippocampus, and are then reactivated during retrieval, yielding the experience of remembering. Whereas most prior neuroimaging studies on reactivation have focused on the reactivation of sets or categories of items, the current study sought to identify cortical patterns pertaining to memory for individual scenes. During encoding, participants viewed pictures of scenes paired with matching labels (e.g., “barn,” “tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
143
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(169 citation statements)
references
References 57 publications
25
143
1
Order By: Relevance
“…Only a few recent studies have sampled a range of "above-threshold" recollective experiences. These studies have shown that reactivation reflects the vividness of recall , the amount of information recollected about a stimulus' features (Wing et al, 2015), and the context in which that stimulus was encoded (Leiker & Johnson, 2014). Together with our own observations, these findings suggest that subjective indices of recollection and pattern reactivation are two facets of a common underlying set of neural memory processes.…”
Section: Summary Of Findingssupporting
confidence: 78%
See 1 more Smart Citation
“…Only a few recent studies have sampled a range of "above-threshold" recollective experiences. These studies have shown that reactivation reflects the vividness of recall , the amount of information recollected about a stimulus' features (Wing et al, 2015), and the context in which that stimulus was encoded (Leiker & Johnson, 2014). Together with our own observations, these findings suggest that subjective indices of recollection and pattern reactivation are two facets of a common underlying set of neural memory processes.…”
Section: Summary Of Findingssupporting
confidence: 78%
“…Johnson, Kuhl, Mitchell, Ankudowich, and Durbin (2015) have shown that aging influences correlations between classification accuracy and vividness of recall across brain ROIs. Wing, Ritchey, and Cabeza (2015) have also shown that stimulus-specific reactivation increases linearly as a function of the number of details recalled for consciously retrieved images. These findings suggest that recollection and reactivation are different facets (one subjective, one objective) of the same underlying brain processes, but more evidence is needed.…”
Section: Introductionmentioning
confidence: 88%
“…Transfer appropriate processing refers to the idea that "memories are represented in terms of the cognitive operations engaged by an event as it is initially processed, and that successful memory retrieval occurs when those earlier operations are recapitulated" (Rugg et al 2008: 340; see also Danker and Anderson 2010;Roediger et al 2002;Roediger and Guynn 1996;Tulving and Thompson 1973;Wing et al 2015). This means a person's memory for recently learned information is linked to representations of the perceptual and cognitive activities that were engaged in when acquiring the information earlier.…”
Section: Transfer Appropriate Processingmentioning
confidence: 99%
“…It has been demonstrated that successful memory decisions are associated with stronger reinstatement signatures in content-specific cortical regions (Bosch et al, 2014; Johnson et al, 2009; Kuhl and Chun, 2014; LaRocque et al, 2013; Polyn et al, 2005; Ritchey et al, 2012; Staresina et al, 2012; Wing et al, 2015). However, the behavioral link between memory decisions and hippocampal pattern completion has yet to be observed.…”
mentioning
confidence: 99%
“…It has been demonstrated that the magnitude of hippocampal BOLD activation during both encoding and retrieval scales with reinstatement signatures in neocortex (Gordon et al, 2014; Horner et al, 2015; Ritchey et al, 2012; Wing et al, 2015). Such findings suggest that the hippocampus plays an important role in the re-experiencing of mnemonic content by influencing cortical reinstatement.…”
mentioning
confidence: 99%